ANALYSIS OF BIOLOGY LEARNING MEDIA FOR CLASS X STUDENTS IN BLITAR CITY - Nita Oktaviani; Dwi Kameluh Agustina; Devita Sulistiana (JOSAR (Journal of Students Academic Research), 2019)
The results of preliminary observations on three high school / MA schools in Blitar City with 71 respondents through questionnaires revealed that the use of instructional media with a percentage of 28.40% was classified as unfavorable and the results of interviews with Biology students stated that 50% with the category was quite difficult to understand Biology material. In this study, researchers analyzed the importance of learning media needs for biology class X students. Research is only limited to the media used when learning Biology. The population in this study was three schools with 71 respondents, with a sample of 33 schools. This study uses a quantitative descriptive approach to the type of survey research. Data from the questionnaire analysis of 50% of 71 respondents stated that biology was difficult to understand because of the large amount of material and the foreign terms they had just heard. The results of the analysis of learning media needs of the use of electronic media that are still much in demand are LCD 95.77%, picture learning media 35.21%, learning media chart 12.67% and video learning media 23.94%. As for what is rarely used is 2.81% radio learning media and the use of posters that have never been applied to biology learning.